Bailar sobre los escombros: colectivizando el luto, compartiendo el dolor - Bonomini Martínez, Sandra (2022)
This article deals with the dialogue and discussion with the performance Insufflation of a Chronic Death by the Women in Quarantine project, São Paulo, Brazil, presented in 2020 during the Covid-19 pandemic. The notions of collectivity and care are highlighted as attributes that, both in art and in life, can contribute by helping us transform pain and think radically about a possible re-existence. Based on counter-hegemonic feminist perspectives and the assessment of one's own experience as knowledge, the author's performance and autobiographical accounts are proposed as micropolitical spaces of resistance and possibility in the face of the situation of precariousness, uncertainty, and violence after the pandemic period in Brazil. Starting from the need to share pain and to collectivize mourning, this creation process is suggested as an anti-capitalist space-time and an enabler of returning life to its status of a dignified life.